Eicosanoid signalling pathways in the development and progression of colorectal cancer: novel approaches for prevention/intervention - Cathcart, Mary-Clare; Lysaght, Joanne; Pidgeon, Graham P. (Cancer and metastasis reviews, 2011)
Arachidonic acid metabolism through cyclooxygenase (COX), lipoxygenase (LOX) and cytochrome P -450 epoxygenase (EPOX) pathways leads to the generation of biologically active eicosanoids, including prostanoids, leukotrienes, hydroxyeicosatetraenoic acid, epoxyeicosatrienoic acid and hydroperoxyeicosatetraenoic acids. Eicosanoid expression levels vary during tumor development and progression of a range of malignancies, including colorectal cancer. The actions of these autocoids are also directly influenced by diet, as demonstrated by recent evidence for omega-3 fatty acids in colorectal cancer (CRC) prevention and/or treatment. Eicosanoids regulate CRC development and progression, while inhibition of these pathways has generally been shown to inhibit tumor growth/progression. A progressive sequence of colorectal cancer development has been identified, ranging from normal colon, to colitis, dysplasia, and carcinoma. While both COX and LOX inhibition are both promising candidates for colorectal cancer prevention and/or treatment, there is an urgent need to understand the mechanisms through which these signalling pathways mediate their effects on tumorigenesis. This will allow identification of safer, more effective strategies for colorectal cancer prevention and/or treatment. In particular, binding to/signalling through prostanoid receptors have recently been the subject of considerable interest in this area. In this review, we discuss the role of the eicosanoid signalling pathways in the development and progression of colorectal cancer. We discuss the effects of the eicosanoids on tumor cell proliferation, their roles in cell death induction, effects on angiogenesis, migration, invasion and their regulation of the immune response. Signal transduction pathways involved in these processes are also discussed. Finally, novel approaches targeting these arachidonic acid-derived eicosanoids (using pharmacological or natural agents) for chemoprevention and/or treatment of colorectal cancer are outlined.